Optimizing laser scanning positions in buildings exteriors: heritage building application - Metawie, Mahmoud; Marzouk, Mohamed (Journal of Civil Engineering and Management, 2020)
Digital documentation for heritage buildings is one of the methods of preserving them as it provides a current record for the buildings. Digital records of heritage buildings can be used for future building rehabilitation, or be presented to the public to raise the awareness, increase tourism and decrease vandalism. This paper focuses on scanning object geometry factor to increase the quality of heritage’s façade point cloud. It optimizes the scanner locations and the scanner field of view to increase the point cloud quality and shorten the scanning time while guaranteeing a set of quality constraints for the point cloud. The quality constraints are based on the incidence angle between the scanned surface and the laser beam, and the max spacing between points. Three different multi-objective optimization algorithms are utilized: 1) genetic algorithm, 2) Jaya algorithm, and 3) particle swarm optimization to increase the quality. Optimization performance measures are adopted to compare the outputs of the optimization algorithms. A multi-criteria decision-making technique (Weighed sum model) is used to choose the optimum solution between the Pareto frontier solutions. Optimization algorithms minimize point cloud density and scanning time while assuring a required point spacing and max incidence angle by changing distance between laser scanner and scanned Facade, horizontal and vertical scan repetitions, and scanner different resolutions. The Jaya algorithm generates the most diversifiable optimal solutions and it is the fastest of the three algorithms considered. This research focuses on vertical building façade and future research will include the all types of Heritage façade. Omar Tosson Palace in Egypt is considered as a case study to demonstrate the use of the developed methodology and to illustrate its essential features.First published online 25 February 2020